2000
DOI: 10.1159/000010274
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Use of Cesarean Section for the Second Twin?

Abstract: Background: In Sweden, the frequency of cesarean section of the second twin after vaginal birth of the first twin has increased in recent years. Methods: To investigate the indications for second twin cesarean sections, all twin deliveries at Huddinge University Hospital from 1995 to 1997 were reviewed retrospectively. The rates of cesarean section for the second twin were compared with figures from the whole country, based on the Swedish medical birth register. Results: Thirty-one percent of all twin deliveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Our observation regarding the distribution of fetal presentations is consistent with that of other studies [21,22]. Perinatal outcome of the second twin was unfavorable in vertex-vertex presentation than that in other two presentations.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation regarding the distribution of fetal presentations is consistent with that of other studies [21,22]. Perinatal outcome of the second twin was unfavorable in vertex-vertex presentation than that in other two presentations.…”
Section: Discussionsupporting
confidence: 92%
“…[48][49][50][51] Whereas this increase may reflect the threat of litigation, we believe it more likely reflects the lack of training and/or experience on the part of obstetricians.…”
Section: The Practice Of a Combined Deliverymentioning
confidence: 99%
“…Wolff also reviewed the indication and outcome of cesarean section for the second twin after vaginal delivery of the first twin in a recent series. 48 Two thirds of the cesarean sections for the second twin were considered potentially avoidable. Of note, in these avoidable cases, no attempt at extraction of the second twin was made before cesarean delivery.…”
Section: Vaginal Delivery Of Twins 161mentioning
confidence: 99%
“…Similar to the management of second stage in singleton pregnancies, any attempts to limit the twin-to-twin delivery interval by an arbitrarily defined cutoff undoubtedly increases the use of instrumental delivery or caesarean section, which may result in unnecessary fetal and maternal morbidities 7 . More recent studies have shown there is no increased risk in perinatal mortality 8 -10 or reduction in Apgar scores 11,12 of the second twin when the delivery interval was prolonged.…”
Section: Introductionmentioning
confidence: 99%